Evaluation of ADA HbA1c criteria in the diagnosis of pre-diabetes and diabetes in a population of Chinese adolescents and young adults at high risk for diabetes: a cross-sectional study. Issue 8 (8th August 2018) - Li, Ge; Han, Lanwen; Wang, Yonghui; Zhao, Yanglu; Li, Yu; Fu, Junling; Li, Ming; Gao, Shan; Willi, Steven M
Abstract : Objective: We aimed to assess haemoglobin A1c (HbA1c) for the diagnosis of pre-diabetes and diabetes in a population of Chinese youths at risk of metabolic syndrome. Setting: Beijing, China. Participants: A total of 581 subjects aged 14–28 years underwent evaluation including an oral glucose tolerance test (OGTT). Insulin sensitivity, β-cell function and a number of cardiovascular disease risk factors were evaluated. Receiver operating characteristic (ROC) curves were used to assess the screening efficacy of HbA1c. Results: Using OGTT data as a standard, the majority (70.0%, 7/10) of subjects with diabetes would have been diagnosed with HbA1c ≥6.5%. In contrast, only 28.1% (16/57) of subjects with pre-diabetes possessed elevated HbA1cs, while the majority (68.4%) had normal HbA1cs. On the contrary, a total of 8.1% (39/479) of youths in the normal HbA1c category (<5.7%) and 21.3% in the pre-diabetes category had pre-diabetes. In the ROC analysis, the area under the curve (AUC) for HbA1c identifying pre-diabetes was 0.680(95% CI 0.640 to 0.719); the optimal threshold was 5.5%, with a sensitivity of 61.4% and specificity of 68.5%. For type 2 diabetes mellitus, the AUC for HbA1c was 0.970 (0.952 to 0.982), and the optimal threshold was 6.1%, with a sensitivity of 90.0% and a specificity of 98.7%. Applying these new cut-offs, pre-diabetic participants (HbA1c 5.5%–6.1%) had lower disposition index and higher risk of dyslipidaemia (OR=1.61, 95% CI 1.10 to 2.37) and metabolic syndrome (OR=2.09, 1.27 to 3.45) than those with normal HbA1c (<5.5%). Conclusion: The American Diabetes Association's established HbA1c criteria for pre-diabetes and diabetes (5.7% and 6.5%) may not be appropriately applied to adolescents and young adults in China. Our findings suggest that those with HbA1c of 5.5%–6.1% already exhibit impaired β-cell function and increased cardiometabolic risk factors which may warrant intervention. Trial registration number: NCT03421444 .